E-Learning Models Analysis for Lifelong Learning - Synytsya, K.M. (Кибернетика и вычислительная техника, 2017)
Introduction. E-learning models reflect various aspects of ICT application in education but they are not intended for reflecting long periods of time, multiple sources of information and knowledge involved or dynamic control from the learner’s side. These and other features are important for lifelong learning modeling aimed at raising the efficiency of learning by the use of individual learner’s data. The purpose of the paper is to review e-learning models that describe frameworks, abstract architectures or reference models for identification of potential prototype for lifelong e-learning model and to outline the requirements to its construction. Results. The study reveals typical features of the e-learning models grouped according to the level of abstraction and connection to technology and pedagogy. The paper presents an overview of lifelong learning specifics and models that could be considered during the lifelong e-learning modeling. Although none of the discussed models could serve as a unique prototype, some of them could either be integrated in a lifelong e-learning model or guide the modeling. A set of requirements to lifelong e-learning model is suggested. Conclusion. Lifelong e-learning model should be presented as a set of views that are relevant to actors in e-learning and reflect longevity, multiple sources, context of learning, management and learner’s control, collection and sharing the data about learning. The main purpose of it could be in identification of components, tools and processes that should be implemented for intelligent and efficient lifelong learning support Дана краткая характеристика моделей электронного обучения и выделены основные группы, на базе которых может быть создана модель электронного обучения на протяжении жизни. Рассмотрены специфические черты непрерывного обучения, определяющие требования к такой модели. Показано, что такая модель должна содержать несколько проекций, отображающих видение обучаемого, разработчика, поставщика учебных услуг, системы образования в целом, быть технологически и педагогически нейтральной и учитывать задачи управления, связанные с изменением условий и целей обучения. Предложена модификация модели Хана для отображения процесса непрерывного обучения, которая заключатся в расширении и адаптации интерпретации компонентов этой модели за счет определения их предназначения при индивидуально-ориентированном моделировании и формировании структуры их взаимодействия. Отмечено, что основная цель модели непрерывного обучения в электронном образовании заключается не только в интеграции частичных моделей в общей схеме, а и в идентификации компонентов, инструментов и процессов, необходимых для реализации интеллектуальной и эффективной подержки обучения на протяжении всей жизни. Наведено коротку характеристику моделей електронного навчання та визначено основні групи, на базі яких є можливим створення моделі неперервного електронного навчання. Розглянуто специфічні характеристики неперервного навчання, які визначають вимоги до такої моделі. Показано, що така модель має містити кілька проекцій, які відображають точку зору учня, розробника, постачальника навчальних послуг, системи освіти в цілому, бути технологічно і педагогічно нейтральною та враховувати проблеми керування, пов’язані зі змінами умов та мети навчання. Запропоновано розвиток моделі Хана для відображення процесу неперервного навчання, що полягає у розширенні та адаптуванні інтерпретації компонентів цієї моделі за рахунок визначення їх призначення в умовах особистісно-орієнтованого моделювання, а також формування структури їх взаємодії. Зазначено, що головна мета моделі неперервного навчання в електронній освіті полягатиме не тільки у поєднанні часткових моделей в загальній схемі, а і в ідентифікації компонентів, інструментів і процесів, які слід запровадити для інтелектуальної та ефективної підтримки навчання протягом усього життя.